Ontogenetic changes in green turtle (Chelonia mydas) diet and home range in a tropical lagoon - Vanderklift, Mathew A.; Pillans, Richard D.; Rochester, Wayne; Stubbs, Jessica L.; Skrzypek, Grzegorz; Tucker, Anton D.; Whiting, Scott D. (Frontiers in Ecology and Evolution, 2023)
Ontogenetic changes in habitat and diet are widespread among marine species. Most species of sea turtles are characterised by extreme ontogenetic changes in habitat use and diet, with large changes occurring in early developmental stages (e.g., neonates to juveniles). Changes can continue even after recruitment to shallow coastal habitats. In places where substantial transitions in habitat occur across short distances, it is possible that the distances of developmental movements from one habitat to another could be comparably short. We investigated ontogenetic changes in home range size, home range location and diet of Chelonia mydas in a tropical coastal lagoon in north-western Australia by combining acoustic telemetry with stable isotope analysis. There was a substantial (but nonlinear) increase in home-range size (kernel utilisation distribution: KUD) with length, and an increase in the average distance of the centre of home ranges from shore with length: larger turtles tended to occupy larger areas further from the shore. These patterns were accompanied by complex nonlinear changes in δ13C, δ15N and δ34S of red blood cells and nails; changes were rapid from 36 cm (the length of the smallest individual captured) to 50 cm, before reversing more gradually with increasing size. δ15N and δ34S (but not δ13C) of red blood cells and nails increased monotonically with KUD and distance from shore. Seagrass was likely an important food for all sizes, macroalgae was potentially important for small (< 60 cm CCL) individuals, and the proportion of jellyfish in diet increased monotonically with size. The combination of acoustic telemetry and stable isotope analysis revealed ontogenetic shifts in use of space and diet across short distances in a tropical coastal lagoon.